Corruption and Economic Growth In Tunisia: Direct or Indirect Effects? - Akrout, Zied (International Journal of Economics and Financial Issues, 2020)
In the post 2011 revolutionary period, Tunisia was engaged in a strategy of development despite the significant difficulties caused by economic growth and chronic corruption. In fact, an increased effectiveness of the said strategy thus calls for a better understanding of this impediment to the development characterized by corruption, in particular in terms of its implications for economic growth. The purpose of this study is therefore to perform an empirical analysis of the effects of corruption on economic growth in Tunisia. As part of formalization inspired by the theory of endogenous growth, and the time series data from BM and ICRG scores over the 1988/2017 period, using a error-correcting model, we estimated the different modalities of the effects of corruption on economic growth. In fact, the obtained results confirm the long-term existence of a direct negative relationship between corruption and economic growth, which implies that an increase of the level of corruption leads to a reduction of GDP. On the other hand, the estimates also revealed that, in the long term, corruption indirectly affects economic growth through different channels, namely the private capital stock, total public expenditure, and the number of students enrolled in primary schools. Our results also showed that corruption has no effect on economic growth in the short term, both directly and indirectly. Keywords: corruption, economic growth, distortion, time series, Tunisia JEL Classifications: D73, O4, C01, O5 DOI: https://doi.org/10.32479/ijefi.10621